Peran Organisasi Remaja Masjid Jami Al-Muhajirin Dalam Mencegah Kenakalan Remaja di RW 20 Depok II Tengah - Adzra Hasna Azzah Haura; Muhammad Fahri; H.M.Kholil Nawawi (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study was to describe the role of the Jami Al-Muhajirin Mosque Youth Organization in Preventing Juvenile Delinquency in Rw 20 Central Depok II. The method used in this study is a qualitative method and included in the type of case study research. Data collection procedures that researchers do is by observations, interviews and documentation. The results og the research in this thesis show that the forms of Juvenile Delinquency in Rw 20 Central Depok Iiare that there are groups of teenagers who gamble online, stay up late, get drunk, take drugs, gatherbuselessly and dress immodestly. The causes of juvenile delinquency are family, friends, entertainment. The role of the youth organizationof the Jami Al-Muhajirin Mosque is a place for creativity, a gathering place, maintaning closeness between mosque youth, taking direct action, intensive invitation and disseminating information. Even thought it has not been considered successful, the Youth of Jami Al-Muhajirin Mosque RW 20 Central Depok II have set good example for youth in society. Keywords: The role of organizations, prevention, juvenile delinquency